Ideological Commitment in Modern African Poetry: Redefining Cultural Aesthetics in Selected Poems of Niyi Osundare’s The Eye of the Earth and Village Voice - Raphael Chukwuemeka Onyejizu; Uchenna Frances Obi (Journal of Language and Literature, 2020)
In this study, ideological commitment to cultural norms is a standpoint that has led to the development of modern African poetry. The Modern African poet is seen as an advocate for cultural prowess and transformation and as such naturally adopts this African traditional antecedent in his poems. Several critical studies on the two collections have focused on the stylistic and literary values of Osundare’s craft without appropriate reviews on the poet's use of cultural forms to reflect his ideological stance on pertinent issues affecting the society. The descriptive qualitative content analysis method was used to show how the selected poems reflect Homi Bhabha’s postcolonial theory of hybridity as expressed through the shifting of cultural margins in the society, thus, illustrating the use of cultural art forms as a means of appreciating nature and exploring issues of exploitation and marginalization. The study also examines the influence of the traditional Yoruba African culture on the poet with an adequate focus on the content and devices of orature, proverbs, riddles, parables, humor, satire, and traditional forms of language. The study submits that the poet adequately incorporated the ideals of culture and its elements in his enduring craft showing his allegiance to his folk cultural patterns.